Gaps in the screening process for women diagnosed with cervical cancer in four diverse US health care settings - Chun R. Chao; Jessica Chubak; Elisabeth F. Beaber; Aruna Kamineni; Connie Mao; Michael J. Silverberg; Jasmin A. Tiro; Celette Skinner; Michael Garcia; Douglas A. Corley; Rachel L. Winer; Tina Raine‐Bennett; et al. (Cancer Medicine)
Abstract Background Potential care gaps in the cervical cancer screening process among women diagnosed with cervical cancer in an era with increased human papillomavirus (HPV) testing have not been extensively evaluated. Methods Women diagnosed with cervical cancer between ages 21 and 65 at four study sites between 2010 and 2014 were included. Screening histories were ascertained from 0.5 to 4 years prior to cervical cancer diagnosis. We identified potential care gaps in the screening history for each woman and classified them into one of three mutually exclusive types: lack of a screening test, screening test failure, and diagnostic/treatment care gap. Distributions of care gaps were tabulated by stage, histology, and study site. Multivariable nominal logistic regression was used to examine the associations between demographic and cancer characteristics and type of care gap. Results Of 499 women evaluated, 46% lacked a screening test in the time window examined, 31% experienced a screening test failure, and 22% experienced a diagnostic/treatment care gap. More than half of the women with advanced cancer and squamous cell carcinoma lacked a screening test compared to 31% and 24% of women with localized cancer and adenocarcinoma, respectively. Women aged 21–29 at diagnosis were more likely to experience screening test failure and diagnostic/treatment care gap, while those aged 50–65 were more likely to lack a screening test, compared to women aged 30–39. Conclusions Our findings demonstrate a continuing need to develop interventions targeting unscreened and under‐screened women and improve detection and diagnosis of adenocarcinoma in women undergoing cervical cancer screening and diagnostic follow‐up.